THE COMMUNICATIVE DIMENSION OF ECONOMIC ACTIVITY IN THE CULTURE OF INDUSTRIAL SOCIETY - Sidorkina, Olena (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2025)
Human economic communication covers various dimensions: the realm of human society, relationships with other individuals, interactions with the natural environment, and engagement with the supernatural world. To philosophically comprehend the essence of the new cultural phenomenon of the Western world-economic man (Homo economicus) – it is essential to characterize the time of its emergence (modern history) as a social phenomenon. The aim of the article is to study the communicative dimensions of economic activity in the culture of an industrial society. Research methods encompass a dialectical approach, emphasizing the principle of the unity of logical and historical, along with socio-cultural determinism. Additionally, the principles of the systemic approach, communication theory, phenomenology are used. Research results.The communicative activity of the economic man of the New Age was carried out in the context of two domains of interaction: communication with the Supernatural and interaction with people who constituted a certain society. Such communication was also carried out through the prism of religious experience. Discussion. From a socio-philosophical point of view, the cultural phenomenon of Homo economicus, as well as the nature of his communicative processes, and its peculiarities, are primarily a social phenomenon of a concrete-historical character. This understanding is based on the relationship between the individual and the collective (social) in the essential nature of a person. The concept of the economic man inherently assumes the presence of others and views human essence as the product of active interaction with the socio-historical whole. Within this framework, objectification takes place. Conclusions. Analyzing the formation of the communicative dimension of economic activity in industrial society, we define the "economic man" as a socio-cultural phenomenon reflected in political economy, sociology, philosophy, and fiction. This phenomenon is evident in two aspects: the individual’s social and personal experience embodied in practical activity and self-reflection on life, socio-economic status, and relationships with the world. A socio-philosophical understanding of the communicative component of economic activity is essential, as the core principles and mechanisms of communication from the industrial era persist in the information society, helping to refine the communicative foundations of economic success